MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI INTERAKSI MAKHLUK HIDUP DAN LINGKUNGANNYA MENGGUNAKAN MODEL KOOPERATIF TIPE STAD BERBANTUAN VIDEO DI KELAS VII A SMP - Dewi Yahayu; Kurnia Ningsih; Titin Titin (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2020)
This study aimed to improve students’ learning outcomes through video-assisted STAD of cooperative learning types. The topic of study was the interaction between living things and their environment, which taught in the class of VII A SMP Islam Bawari, Pontianak. This research adopted a classroom action research (CAR) with two cycles which executed in two meetings. Each cycle consisted of four stages: planning, action, observation, and reflection. The instrument for data collection included learning observation sheets and learning achievement test. In the implementation of the video-assisted STAD model, all stages in cycle I and II were entirely (100%) implemented following the planned learning design. The average student learning outcomes increased from 77.00 (cycle I) to 86.60 (cycle II) with the percentage of completeness (Kriteria Ketuntasan Minimal, KKM) of 76% and 92% for the cycle I and II, respectively. Overall, the implementation of STAD, which was assisted by the video, succesfully improved students’ learning outcomes on the topic of interaction between living things and their environment of class class VII A SMP Islam Bawari.